Innovation on Firm Performance: A Systematic Literature Review - Mutiara Fitridiani; Masduki Asbari (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
The research reviews three significant studies that investigate the impact of innovation on firm performance and corporate social responsibility (CSR) in different contexts: Vietnamese manufacturing firms, the role of information technology (IT) innovation in Kenya, and the synergy effects of innovation on overall performance. The first study examines how innovative practices within Vietnamese manufacturing firms lead to enhanced operational efficiency and stronger CSR commitments, suggesting that firms can achieve competitive advantages while addressing societal needs. The second study highlights the role of IT innovation in Kenya, showcasing how firms that adopt digital technologies experience substantial improvements in productivity, operational efficiency, and customer engagement, which are crucial for success in a fast-paced market environment. Lastly, the third study explores the synergy effects of innovation, indicating that organizations implementing a comprehensive innovation strategy that integrates product, process, and market innovations tend to achieve superior performance outcomes. This review emphasizes the critical importance of innovation as both a driver of economic success and a facilitator of social responsibility, advocating for a holistic approach to innovation that aligns with sustainable business practices to create shared value for stakeholders.